Análise da viabilidade de molas de nitinol como atuadores lineares em uma prótese de mão com uso em modelo CAD - Vilseke, Abel José (2021)
Hand prostheses that are described in the literature, designed to reproduce natural gripping movements, are provided with angular actuators associated to transmission elements such as cables, bars or gears. The mechanical configurations, commonly applied in prostheses, restrict the mobility of the fingers to the condition of flexion or extension proportionally distributed among the links of the mechanism that correspond to the phalanges, limiting the possibility of reproducing independent movements between the proximal and medial phalanges and between the metacarpal and the proximal phalanges. This research is about the development of an ideal hand model in 3D modeling software that enables the assessment of independent mobility among the phalanges using small Nitinol orthodontic springs as actuators, installed in pairs for each finger joint. To carry out this study, it was necessary to determinate dimensional characteristics of the mechanical components of the prosthesis and the positioning of the springs, simulating the variation in the length of the springs under temperature variation by the Joule effect, as well as the load capacity exerted during contraction and relaxation of the bionic limb. The results show that the individual movement of the joints is achieved, but the mechanical energy developed by the actuators tested in this research is inferior to all the data observed in the angular motors application reported.